2020
DOI: 10.1080/01596306.2020.1843113
|View full text |Cite
|
Sign up to set email alerts
|

Toward a framework for assessing the ‘global’ and ‘citizen’ in global citizenship education in Australia and beyond

Abstract: In addition to its influences across economic, geopolitical, and social spheres, globalization has given rise to the notion of a 'global citizen' who is able to understand a shifting and more internationalized world while moving fluidly through it. Education has been trumpeted as the means to achieve this globally-aware citizenry, leading to an entire field of global citizenship education (GCE). Here teachers are the linchpin, yet understandings of globally-focused coursework in teacher education remain underd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 42 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In a sense, EFL education is a project of emancipation (Giroux, 2020) as the young generation strives to reach the world outside starting from a critical literacy journey that is strewn with ambivalence, complexity and creativity. This study also led us to conclude that dynamics and micro‐politics in the classroom can afford students agency, open mindset and collective identity to explore the global community as global citizens who take action upon our world (Baildon and Damico, 2011; Thomas and Banki, 2020). A critical‐literacy‐informed lens sheds light on how the integrated GCE–EFL agenda can be vigorously enacted to nurture the heart of young learners who are committed to social justice and sustainability of a better planet.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In a sense, EFL education is a project of emancipation (Giroux, 2020) as the young generation strives to reach the world outside starting from a critical literacy journey that is strewn with ambivalence, complexity and creativity. This study also led us to conclude that dynamics and micro‐politics in the classroom can afford students agency, open mindset and collective identity to explore the global community as global citizens who take action upon our world (Baildon and Damico, 2011; Thomas and Banki, 2020). A critical‐literacy‐informed lens sheds light on how the integrated GCE–EFL agenda can be vigorously enacted to nurture the heart of young learners who are committed to social justice and sustainability of a better planet.…”
Section: Discussionmentioning
confidence: 95%
“…In the past decades, as globalisation has swept the world, discourse concerning global citizenship education (GCE) on the research agenda has sprung up as a response to its impact on socio‐economic, political and environmental interdependence (Thomas and Banki, 2020; Torres and Bosio, 2020). In the context of an ever‐increasingly interconnected world, educators are expected to assume the responsibility of fostering young people's global competencies for active and critical engagement with a more diversified and inclusive world (UNESCO, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The role of teachers in building a nation cannot be overemphasized (Timm & Barth, 2021). The development of a conscious citizenry to drive development depends upon the standard of a nation's education system (Thomas & Banki, 2021). Research, over the years, has indicated that teachers have great potentials to affect students' educational outcomes (Madigan & Kim, 2021;Madigan & Curran, 2021).…”
Section: Introductionmentioning
confidence: 99%